Single-Volumed Simple Book:Standards for Bibliographical Reference - Ranganathan, S. R.; Neelameghan, A. (Journal of Information and Knowledge, 2000)
Enumerates the purpose, the place of occurrence, and the items of information necessary for identification, location, and evaluation, of a bibliographical reference. Prescribes rules for the rendering of a bibliographical reference when the referred-to document is the whole of a single-volumed simple book.